2004
DOI: 10.1089/1523086041361686
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized Phospholipids in Oxidized Low-Density Lipoprotein Reduce the Activity of Tissue Factor Pathway Inhibitor Through Association with Its Carboxy-Terminal Region

Abstract: Tissue factor pathway inhibitor (TFPI) is a Kunitz-type protease inhibitor that inhibits the initial reactions of blood coagulation. In this study, we explored the nature of active components that reduce the anticoagulant activity of TFPI in oxidized low-density lipoprotein (ox-LDL). The organic solvent-soluble fraction obtained from ox-LDL was fractionated by normal-phase HPLC. The binding profile of each fraction to TFPI showed a single peak eluting near purified oxidized phospholipid. To explore further the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
33
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 34 publications
1
33
0
1
Order By: Relevance
“…MM-LDL was shown to regulate all of these activities to promote a procoagulant state. 2,28,[39][40][41][42] The signal transduction pathway regulating the induction of TF mRNA levels by Ox-PAPC in HUVEC was shown to be mediated through both a PKC/Erk/EGR-1 pathway and a Ca++/calcineurin/NFAT pathway. 39 Both transcription factors, EGR-1 and NFAT, act together in regulating the TF promoter.…”
Section: Procoagulant Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…MM-LDL was shown to regulate all of these activities to promote a procoagulant state. 2,28,[39][40][41][42] The signal transduction pathway regulating the induction of TF mRNA levels by Ox-PAPC in HUVEC was shown to be mediated through both a PKC/Erk/EGR-1 pathway and a Ca++/calcineurin/NFAT pathway. 39 Both transcription factors, EGR-1 and NFAT, act together in regulating the TF promoter.…”
Section: Procoagulant Activitymentioning
confidence: 99%
“…These studies demonstrate differential regulation of TF and TM transcription by Ox-PAPC, mediated through activation of distinct and separate signaling pathways. In addition, Ox-PAPC was also show to reduce the activity of tissue factor pathway inhibitor (TFPI), a protease inhibitor that inhibits the initial reactions of blood coagulation 42 . In these studies, it was concluded that TFPI activity was inhibited through direct interaction of oxidized lipids with the C-terminal basic region of TFPI.…”
Section: Procoagulant Activitymentioning
confidence: 99%
“…Oxidized phospholipids were also shown to accumulate in atherosclerosis and other chronic inflammatory diseases (5). The increased concentrations of oxidized phospholipids in the injured lung may influence the functions of pulmonary endothelial cells (ECs), including the modulation of pulmonary inflammatory response and EC barrier regulation (6-9).Oxidized phospholipids may induce various proinflammatory effects, including the stimulation of cytokines and chemokine production (10, 11), the activation of cell adhesion molecules (12, 13), the elevation of intracellular and extracellular levels of superoxide radicals in human ECs (14, 15), the activation of coagulation cascades, and platelet activation (16,17). However, in addition to tissue-damaging and proinflammatory effects, oxidized phospholipid products may exhibit potent anti-inflammatory activities under certain conditions.…”
mentioning
confidence: 99%
“…In the atheromatosus lesions the TF is located around the necrotic center rich in lipids, for it is assumed that low density lipoprotein cholesterol (c-LDL) and the oxidized lipids induce the expression of TF (47).…”
Section: Alterations In Hemostasis and Fibrinolysismentioning
confidence: 99%
“…In the atheromatous lesions TF is located around the necrotic center rich in lipids, for it is assumed that c-LDL and the oxidized lipids induce the expression of TF (47). In contrast, PCR associated with inflammatory processes also induces the expression of TF on the cellular surfaces (78).…”
Section: Alterations In Hemostasis and Fibrinolysismentioning
confidence: 99%